“Gestión administrativa y su influencia en la calidad del servicio público de agua potable y alcantarillado del GAD municipal cantón Quevedo, año 2023” - Jaramillo Mejía, Adonis Emerson (2024)
The research project entitled "ADMINISTRATIVE MANAGEMENT AND ITS INFLUENCE ON THE QUALITY OF THE PUBLIC SERVICE OF DRINKING WATER AND SEWERAGE OF THE MUNICIPAL GAD CANTON QUEVEDO, YEAR 2023" For the development of the research, the conceptual, theoretical and legal bases that support the variables of the topic were included, analyzes the administrative management and its influence on the quality of the public service of drinking water and sewerage. Recognizing the importance of the services for the citizens, it was established how administrative decisions influence the availability, accessibility and quality of water, as well as the efficiency of the sewage systems, with repercussions on the well-being of the citizens. The objective is: To analyze the administrative management in the quality of the public service of the Municipal Decentralized Autonomous Government of Quevedo Canton in the year 2023. The research is of an exploratory and descriptive nature, deductive and inductive methods of analysis were used, for which observation guides, interviews and surveys were applied, the data were analyzed through the IBM SPSS Statistics V26 statistical program that allowed determining the Pearson correlation coefficient, which allows measuring the strength and direction of the association of two random quantitative variables with a joint bivariate distribution. Pearson's correlation is a measure that indicates the linear relationship between two variables. Keywords: administrative management, quality, basic services, planning, users.